2019
DOI: 10.3390/molecules24091806
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol and Q-Tubes: Green Catalyst and Technique for Synthesis of Polyfunctionally Substituted Heteroaromatics and Anilines

Abstract: The role of glycerol as a green bio-based solvent, reactant, and/or a catalyst in the synthesis of novel heterocycles, under pressure, is studied. Synthesis of novel quinolines in good yields using a new modified Skraup synthesis, utilizing glycerol and pressure Q-tubes, is demonstrated. Novel aniline trimers are prepared using glycerol, and substituted anilines under pressure, in acidic medium and water. Glycerol was employed as a catalyst and a green solvent in the synthesis of novel pyridazines 13a–c. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Elnagdi and coworkers reported the modified skraup reaction using aniline, sulphuric acid, glycerol, and water in pressure Q‐tubes without the use of oxidizing agents. Glycerol was used as catalyst and solvent that improved the reaction yield and reduced reaction time (Almarzouq & Elnagdi, 2019). Naima et al reported the reaction (Scheme 1) in which they used excess glycerol, concentrated sulfuric acid and iodine as an oxidizing agent at 110°C temperature for 1 h then increased the temperature to 170°C for another hour.…”
Section: Quinoline Scaffoldmentioning
confidence: 99%
“…Elnagdi and coworkers reported the modified skraup reaction using aniline, sulphuric acid, glycerol, and water in pressure Q‐tubes without the use of oxidizing agents. Glycerol was used as catalyst and solvent that improved the reaction yield and reduced reaction time (Almarzouq & Elnagdi, 2019). Naima et al reported the reaction (Scheme 1) in which they used excess glycerol, concentrated sulfuric acid and iodine as an oxidizing agent at 110°C temperature for 1 h then increased the temperature to 170°C for another hour.…”
Section: Quinoline Scaffoldmentioning
confidence: 99%
“…Among these methods, the classic and common methods are the Friedlander, Skraup, Doebner-von Miller and Combes reactions. [5][6][7][8][9] Although these methods have great general applicability and show good conversion for various types of quinoline compounds, the conditions required for their reaction are relatively harsh and the reaction process is complicated and have long steps. The reaction usually requires strong acids, oxidants and other hazardous reagents which adversely affect the environment-friendly chemistry and atom economy.…”
Section: Introductionmentioning
confidence: 99%